2021
DOI: 10.1532/hsf.3975
|View full text |Cite
|
Sign up to set email alerts
|

Is Epicardial Adipose Tissue Associated with Atrial Fibrillation Following Cardiac Surgery? A Systematic Review and Meta-Analysis

Abstract: Background: Although epicardial adipose tissue (EAT) has been proven to be related to atrial fibrillation (AF) and post-ablation AF recurrence, the association between EAT and AF after cardiac surgery (AFACS) remains unclear. Objective: This study was a systematic review and meta-analysis that assessed the relationship between EAT and AFACS. Methods: Electronic databases were systematically searched for “atrial fibrillation” and “epicardial adipose tissue.” The analysis was stratified according to the EAT meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Population studies demonstrate EAT volume is independently associated with AF occurrence, severity, and recurrence, and therefore may mediate the link between obesity and AF. 25 , 26 This association was stronger than those detected for measures of abdominal or overall adipose tissue (including BMI), suggesting a unique role for EAT. 26 Increased LA EAT volume also independently correlated with greater LA fibrosis and dilatation, which are predictors for AF.…”
Section: The Role Of Eat In Afmentioning
confidence: 80%
See 1 more Smart Citation
“…Population studies demonstrate EAT volume is independently associated with AF occurrence, severity, and recurrence, and therefore may mediate the link between obesity and AF. 25 , 26 This association was stronger than those detected for measures of abdominal or overall adipose tissue (including BMI), suggesting a unique role for EAT. 26 Increased LA EAT volume also independently correlated with greater LA fibrosis and dilatation, which are predictors for AF.…”
Section: The Role Of Eat In Afmentioning
confidence: 80%
“… 98 Recently, meta‐analyses have found that EAT was associated with POAF. 25 The underlying mechanism of POAF is not fully elaborated. Possible mechanisms may include pericardial inflammation, including EAT‐mediated interleukin‐6 and MCP‐1 (monocyte chemoattractant protein‐1) signaling, 99 and autonomic imbalance after cardiac surgery.…”
Section: The Effect Of Obesity On Rhythm Controlmentioning
confidence: 99%
“…Therefore, we make it clear that compared with the overall fat environment, changes in the local fat microenvironment of the heart have more critical value for the pathophysiology of AF. (2) For evaluating the change of LA in AF patients, traditional index of LA size or area has been used in most previous studies ( 11 13 ). Nakamori et al confirmed the correlation between EAT and LA remodeling by measuring LA diameter and volume ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…(2) For evaluating the change of LA in AF patients, traditional index of LA size or area has been used in most previous studies ( 11 13 ). Nakamori et al confirmed the correlation between EAT and LA remodeling by measuring LA diameter and volume ( 13 ). In Yorguns’ study, EAT was associated with the presence of AF and the diameter of the LA ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation